Immune Complexes in Juvenile Idiopathic Arthritis - Moore, Terry L. (Frontiers in Immunology, 2016)
Abstract for invited review in “Molecular Mechanisms of Immune Complex Pathophysiology” thematic issue to be published in “Frontiers in Immunology”. “Immune Complexes(IC)in Juvenile Idiopathic Arthritis (JIA)” Terry L. Moore, MD, FAAP, FACR, MACR Professor of Internal Medicine,Pediatrics, and Molecular Biology and Immunology Director of Adult and Pediatric Rheumatology Saint Louis University School of Medicine Saint Louis, Missouri 631`04,USA Juvenile idiopathic arthritis (JIA) reflects a group of clinically heterogeneous, autoimmune disorders in children characterized by chronic arthritis and hallmarked by elevated levels of circulating immune complexes (CICs) and associated complement activation by-products in their sera. ICs have been detected in patients’ sera with JIA utilizing a variety of methods, including the anti-human IgM affinity column,C1q solid phase assay, polyethylene glycol precipitation, Staphylococcal Protein A separation method, anti-C1q/C3 affinity columns, and FcγRIII affinity method. As many as 75% of JIA patients have had IC detected in their sera. The CIC proteome in JIA patients has been examined to elucidate disease-associated proteins that are expressed in active disease. Evaluation of these IC s have shown the presence of multiple peptide fragments by SDS-PAGE and 2-DE. Subsequently, all isotypes of rheumatoid factor (RF), isotypes of anti-cyclic citrullinated (CCP) peptide antibodies, IgG, C1q, C4, C3, and the membrane attack complex (MAC) were detected in these IC. Complement activation and levels of IC correlate with disease activity in JIA, indicating their role in the pathophysiology of the disease. This review will summarize the existing literature and discuss the role of possible protein modification that participates in the generation of immune response. We will address the possible role of these events in the development of ectopic germinal centers that become the secondary site of plasma cell development in JIA. We will further address possible therapeutic modalities that could be instituted as a result of the information gathered by the presence of ICs in JIA.